A breath of information: the volatilome - Mansurova, M.; Ebert, B.E.; Blank, L.M.; Ibáñez, A.J. (Springer Verlag, 2018)
Volatile organic compounds (VOCs) are small molecular mass substances, which exhibit low boiling points and high-vapour pressures. They are ubiquitous in nature and produced by almost any organism of all kingdoms of life. VOCs are involved in many inter- and intraspecies interactions ranging from antimicrobial or fungal effects to plant growth promotion and human taste perception of fermentation products. VOC profiles further reflect the metabolic or phenotypic state of the living organism that produces them. Hence, they can be exploited for non-invasive medicinal diagnoses or industrial fermentation control. Here, we introduce the reader to these diverse applications associated with the monitoring and analysis of VOC emissions. We also present our vision of real-time VOC analysis enabled by newly developed analytical techniques, which will further broaden the use of VOCs in even wider applications. Hence, we foresee a bright future for VOC research and its associated fields of applications.
Keywords: Volatilome; Volatome; Volatile organic compounds (VOCs); Mass spectrometry (MS); Secondary electrospray ionization (SESI); Pheromones; https://purl.org/pe-repo/ocde/ford#1.04.02